Appreciative Inquiry: Bridging Research and Practice in a Hospital Setting. Issue 1 (16th April 2018) - Hung, Lillian; Phinney, Alison; Chaudhury, Habib; Rodney, Paddy; Tabamo, Jenifer; Bohl, Doris
Purpose: In this action study, researchers worked with a team of interdisciplinary practitioners to co-develop knowledge and practice in a medical unit of a large urban hospital in Canada. An appreciative inquiry approach was utilized to guide the project. This article specifically focuses on examining the research experiences of practitioners and their accounts on how the research influenced their practice development to enact person-centered care. Method: The project took place in the hospital's medical unit. A total of 50 staff participants attended focus groups including nursing staff, allied health practitioners, unit leaders, and physicians. One senior hospital administrator was interviewed individually. In total, 36 focus groups were conducted to bring participants together to co-vision and co-develop person-centered care. Results: Analysis of the data produced three themes: (a) appreciating the power of co-inquiry, (b) building team capacity, and (c) continuous development. Furthermore, 10 key enablers for engaging staff in the research process were developed from the data. A conceptual tool, "team Engagement Action Making" (TEAM) has been created to support others to do similar work in practice development. Conclusion: An appreciative inquiry approach has the potential to address gaps in knowledge by revealing ways to take action. Future research should further investigate how the appreciative inquiry approach may be used to support bridging research and practice.